Optimasi Teknik Pengawetan dan Pendampingan GMP untuk Memperpanjang Masa Simpan Produk Gula Aren Niranta - Gumala, Azhoma; Fauzana, Annisa; Komalasari, Sanda Patrisia; Tri, Diwah Ganda; Hadelina, Rizka; Mardiah, Ainul; Irwan, Naufal Rafif; Fadhilah, Rifa; Rahman, Khalilul (Jurnal Hilirisasi IPTEKS, 2025)
Niranta is a micro palm sugar processing business in Padang with export potential and high-quality products. However, the business faces challenges with limited shelf life, especially for liquid palm sugar which deteriorates within less than 6 months after opening due to microbial growth and physicochemical changes. This Community Service Program was designed to extend the shelf life of both powdered and liquid palm sugar products through scientific formulation optimization, improved preservation techniques, discussion about appropriate packaging solutions, and adherence to Good Manufacturing Practices. The 8-month program consisted of socialization sessions, hands-on training, technology transfer, and continuous mentoring focused on preservation methods, hygiene standards, and GMP implementation. Key interventions included the addition of sodium benzoate as a preservative in liquid palm sugar, process control using sterilization for packaging, and Good Manufacturing Practices mentoring collaboration with National Agency of Food and Drug Administration (BPOM) Padang. Real-time shelf-life testing was conducted on treated products for over 6 months post-opening. Preliminary results demonstrate significant improvement: liquid palm sugar supplemented with 0.1 % sodium benzoate remained microbiologically and organoleptically stable beyond 6 months. These findings confirm the effectiveness of combined preservation and process control strategies. To ensure long-term sustainability, recommendations include formal collaboration with the National Agency of Drug and Food Control (BPOM) for GMP certification, advanced training for workers, and ongoing accelerated and real-time stability studies.